Self-assembly in casting solutions of block copolymer membranes - Marques, D.; Vainio, U.; Chaparro, N.; Calo, Victor; Bezahd, A.; Pitera, J.; Peinemann, K.; Nunes, S. (RSC Publishing, 2013)
Membranes with exceptional pore regularity and high porosity were obtained from block copolymer solutions. We demonstrate by small-angle X-ray scattering that the order which gives rise to the pore morphology is already incipient in the casting solution. Hexagonal order was confirmed in PS-b-P4VP 175k-b-65k solutions in DMF/THF/dioxane with concentrations as high as 24 wt%, while lamellar structures were obtained in more concentrated solutions in DMF or DMF/dioxane. The change in order has been understood with the support of dissipative particle dynamic modeling. © 2013 The Royal Society of Chemistry.